The Role Of Risk Propensity In Mediating The Influence Of Financial Behavioral Bias On Investment Performance Moderated By Financial Literacy - Budi, Nuryamin; Sarita, Buyung; Sujono, Sujono; Sabrin, Sabrin (Journal of Neonatal Surgery, 2025)
Financial behavioral biases including financial cognitive bias and financial emotional bias, risk propensity and financial literacy are important factors in improving investment performance. By considering the role of each of these factors, investors can make the right decisions and encourage the achievement of investment performance in investors who are active in the Indonesia Stock Exchange representative of Southeast Sulawesi. This study uses a quantitative approach using the SEM PLS analysis tool with Smart PLS 4.0. This study was conducted using a survey method using a questionnaire to 391 investors spread across 17 districts/cities in Southeast Sulawesi province. This study uses panel data, sampling through the probability random sampling method, then determining the sample size through the proportional allocation method. The results of the study indicate that: 1) financial behavioral bias, namely financial cognitive bias and financial emotional bias have a positive and significant effect on risk propensity and investment performance; 2) Risk propensity is proven to act as a mediator in the relationship between financial behavioral bias and investment performance; 3) Financial cognitive bias has a negative effect on investment performance; 4) Financial emotional bias has a positive effect on Investment Performance; 5) Risk propensity has a positive and significant effect on investment performance; 6) The role of financial literacy has a negative and insignificant effect in moderating the effect of risk propensity on investment performance; 7) Financial literacy has a positive and significant effect on investment performance. These findings emphasize the importance of understanding behavioral bias in investment decision making and the role of financial literacy in improving investment performance. This study provides policy implications for practitioners and individual investors